2020
DOI: 10.1038/s41598-019-57111-5
|View full text |Cite
|
Sign up to set email alerts
|

CD8 infiltration is associated with disease control and tobacco exposure in intermediate-risk oropharyngeal cancer

Abstract: Oropharyngeal squamous cell carcinoma (OPSCC) incidence is increasing at a nearly epidemic rate, largely driven by the human papillomavirus (HPV). Despite the generally favorable clinical outcomes of patients with HPV driven (HPV+) OPSCC, a significant subset of HPV tumors associated with tobacco exposure have diminished treatment response and worse survival. The tumor immune microenvironment (TIME) has been shown to be a critical driver of treatment response and oncologic outcomes in OPSCC generally and HPV+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 41 publications
1
25
0
1
Order By: Relevance
“…Our results are consistent with a recent report demonstrating decreased CD8+ IHC staining in tobacco-exposed primary HPV(+) OPSCC tumors. 13 Our investigation elucidates this phenomenon in much greater biologic detail by using a readout with multiple mRNA hybridization probes, validating in IHC, and controlling for mutational burden using our WES data. Multiple groups have described a similar inverse relationship between tobacco exposure and immune infiltration in HPV(-) HSNCC.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Our results are consistent with a recent report demonstrating decreased CD8+ IHC staining in tobacco-exposed primary HPV(+) OPSCC tumors. 13 Our investigation elucidates this phenomenon in much greater biologic detail by using a readout with multiple mRNA hybridization probes, validating in IHC, and controlling for mutational burden using our WES data. Multiple groups have described a similar inverse relationship between tobacco exposure and immune infiltration in HPV(-) HSNCC.…”
Section: Discussionmentioning
confidence: 75%
“…This hypothesis is supported by a recent report demonstrating lower CD8+ immunohistochemical (IHC) staining in tobacco-exposed HPV(+) tumors. 13 No prior investigation has systematically evaluated the molecular features associated with tobacco, comparing both its mutational and tumor immune effects. Using a multi-omics approach, we tested both of these hypotheses in a cohort of HPV(+) OPSCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is also a likely driver of poor outcomes, particularly in the Veteran population with high rates of tobacco use. Smoking worsens prognosis in HPV‐positive OPSCC, increasing the risk of death by 1% for every one pack‐year of smoking 30‐32 . However, to date, few studies have considered the interaction between HIV and HPV in OPSCC, and one previous study of OPSCC among PWLH found no difference in survival by HPV status, 33 This discordance justifies additional examination of the interaction between HPV and HIV in OPSCC specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of TILs was performed on all pretreatment tumor specimens as previously described using conventional immunohistochemistry coupled to quantitative imaging. 30…”
Section: Clinical Datasetmentioning
confidence: 99%
“…We previously reported on TILs as a predictor of oncologic outcomes in Veterans with HNSCC limited to the oropharynx site. 30 In the current study, we performed a secondary analysis of this dataset using clinically annotated data regarding the presence of diabetes mellitus (DM) at the time of cancer diagnosis and metformin utilization at the time of diagnosis and during treatment delivery. Of 143 patients, 21 patients carried a diagnosis of DM; among these, 11 patients were taking metformin at time of diagnosis and during treatment and 10 were utilizing other means of glycemic control.…”
Section: Chronic Metformin Treated Tumors Are Characterized By An Increased Immune Infiltratementioning
confidence: 99%